INDONESIAN TRANSLATOR - JAPANESE USING WEB-BASED SPEECH - Rosandi, Chandra (YHMM PUBLISHING, 2023)
Japanese language is a foreign language as well as English, studied English language difference from elementary through high school. For the Japanese language itself is only a few schools implement it because of the lack of teachers who can speak Japanese. Therefore this program is designed to address the problem. With this program do not have to worry about someone can speak Japanese because the program is equipped with a voice that means someone who wants to speak Japanese need only speak Indonesian to be converted or translated into the Japanese language in sentences and sound the Japanese language. The method used is the method of literature study, observation, analysis of needs.